Uncontrolled Type 2 Diabetes Mellitus Induces an Enterococcus faecalis Lung Abscess: A case report - Aryana, Wayan Ferly; Wibowo, Adityo; Gozali, Achmad; Saputra, Tito Tri; SL, I Made Afryan; Febrihartati, Isura (Medula, 2024)
The incidence of lung abscess has increased due to the rise in antibiotic resistence, aging population, and immunocompromised patients.  Lung abscess is associated with high mortality rates, ranging from 1—20% globally, long treatment cycles, and significant management costs. Diabetes millitus affect innate and adaptive immunity, This dysregulation, microvascular complications, poor vascular flow, can further compromise an appropriate immune response and healing leading to worsening or secondary infections. Uncontrolled diabetes mellitus can lead patients to immunocompromised conditions, predisposing them to infectious disease. This study is a case report with data obtained through self-history, physical examination, and supporting examinations. A 49-year-old female patient presented with complaints of dyspnea, productive cough, and fever. The patient had a history of uncontrolled type 2 diabetes mellitus with fasting blood glucose 219 mg/dL. Chest examination showed a decreased of tactile fremitus on the left lung field, dullness on percussion of the left lung field, and decreased vesicular sound on auscultation of the left lung field. Laboratory and radiological examinations were also carried out. The CT show a well-demarcated lesion measuring 13.1x7.2x11.2 cm, air-fluid level (+), walled 0.5 cm thick  indicating suspicion of left lung abscess. The patient received treatments and showed clinical improvement so that therapy could be continued on an outpatient basis.